Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1016/j.bpj.2011.11.4016
|View full text |Cite
|
Sign up to set email alerts
|

α−α Cross-Links Increase Fibrin Fiber Elasticity and Stiffness

Abstract: Fibrin fibers, which are ~100 nm in diameter, are the major structural component of a blood clot. The mechanical properties of single fibrin fibers determine the behavior of a blood clot and, thus, have a critical influence on heart attacks, strokes, and embolisms. Cross-linking is thought to fortify blood clots; though, the role of α-α cross-links in fibrin fiber assembly and their effect on the mechanical properties of single fibrin fibers are poorly understood. To address this knowledge gap, we used a combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(107 citation statements)
references
References 39 publications
4
99
0
Order By: Relevance
“…The major targets of FXIII(a) activity are the fibrin γ-and α-chains, and FXIII(a)-mediated crosslinking of these fibrin chains imparts critical structural and mechanical properties to the fibrin network. Compared with uncrosslinked fibers, crosslinked fibers are thinner and more elastic (37,38) and require greater force to rupture (39). Compared with uncrosslinked clots, crosslinked clots have smaller pores, increased network density, and a higher viscoelastic storage modulus (ref.…”
Section: Discussionmentioning
confidence: 99%
“…The major targets of FXIII(a) activity are the fibrin γ-and α-chains, and FXIII(a)-mediated crosslinking of these fibrin chains imparts critical structural and mechanical properties to the fibrin network. Compared with uncrosslinked fibers, crosslinked fibers are thinner and more elastic (37,38) and require greater force to rupture (39). Compared with uncrosslinked clots, crosslinked clots have smaller pores, increased network density, and a higher viscoelastic storage modulus (ref.…”
Section: Discussionmentioning
confidence: 99%
“…These studies used whole clot rheology by torsion pendulum [30] and single fibre measurement by atomic microscopy [33], and showed an increase in fibre and clot stiffness of around 40% due to -chain cross-linking.…”
Section: Fibrin - Chains Cross-linkingmentioning
confidence: 99%
“…8,30,37 Studies with native fibrinogen vs the mutant (gQ398N, gQ399N, and gK406R) have revealed independent contributions coming from a-a crosslinks. 16,38 Such crosslinks play major roles in promoting clot stiffness, fiber straightening, and hindering fibrinolysis.…”
Section: Introductionmentioning
confidence: 99%